Zróżnicowanie produkcyjno-ekonomiczne gospodarstw rodzinnych w zależności od wielkości stada krów mlecznych - Radwan, Andrzej; Piecuch, Jakub (Production and Economic Diversification of Family Farms Depending on Dairy Cow Herd, 2006)
The work is an analysis of production and economic results generated by developing farms of various sizes of cow herds selected purposefully. The basic source of data are results of surveys conducted in the Wydmiany municipality in the Warmia and Mazury region. The studies show that the best production and economic results have been generated on farms focused mainly on milk production on a large scale. The factor favouring improvement in production profitability is production of own fodder - cereals and green forage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 273-278